Iron-catalysed enantioconvergent Suzuki–Miyaura cross-coupling to afford enantioenriched 1, 1-diarylalkanes. Issue 93 (6th November 2020) - Tyrol, Chet C.; Yone, Nang S.; Gallin, Connor F.; Byers, Jeffery A.
Abstract : The first stereoconvergent Suzuki–Miyaura cross-coupling reaction was developed to afford enantioenriched 1, 1-diarylalkanes. Abstract : The first stereoconvergent Suzuki–Miyaura cross-coupling reaction was developed to afford enantioenriched 1, 1-diarylalkanes. An iron-based complex containing a chiral cyanobis(oxazoline) ligand framework was best to obtain enantioenriched 1, 1-diarylalkanes from cross-coupling reactions between unactivated aryl boronic esters and benzylic chlorides. Enhanced yields were obtained when 1, 3, 5-trimethoxybenzene was used as an additive, which is hypothesized to extend the lifetime of the iron-based catalyst. Exceptional enantioselectivities were obtained with challenging ortho -substituted benzylic chlorides.